Electrode considerations, excitation methods and measurement techniques for electrical impedance tomography - Venkatratnam C.; Farrukh N. (Springer Verlag, 2023)
Biomedical engineering; Electric impedance; Electric impedance measurement; Electric impedance tomography; Statistics; Tomography; Adjacent method; Electrical impe dance tomography (EIT); Electrical impedance tomography; Electrode distances; Measurement techniques; Multiplexer; Reconstructed image; Standard deviation; Electrodes